Monocytic-Myeloid Derived Suppressor Cells of HIV-Infected Individuals With Viral Suppression Exhibit Suppressed Innate Immunity to Mycobacterium tuberculosis - Namdev, Priyanka; Patel, Shiv; Sparling, Brandi; Garg, Ankita (Frontiers in Immunology, 2021)
Tuberculosis can occur during any stage of Human Immunodeficiency virus 1 (HIV) -infection including times when CD4+ T cell numbers have reconstituted and viral replication suppressed. We have previously shown that CD11b+CD33+CD14+HLA-DR-/lo myeloid-derived suppressor cells (MDSC) persist in HIV-infected individuals on combined anti-retroviral therapy (cART) and with virologic suppression. The response of MDSC to Mycobacterium tuberculosis (Mtb) is not known. In this study, we compared the anti-mycobacterial activity of MDSC isolated from HIV –infected individuals on cART with virologic suppression (HIV MDSC) and HIV-uninfected healthy controls (HIV-ve MDSC). Compared to HIV-ve MDSC, HIV MDSC produced significantly less quantities of anti-mycobacterial cytokines IL-12p70 and TNFα, and reactive oxygen species when cultured with infectious Mtb or Mtb antigens. Furthermore, HIV MDSC showed changes in the Toll-like receptor and IL-27 signaling, including reduced expression of MyD88 and higher levels of IL-27. Neutralizing IL-27 and overexpression of MyD88 synergistically controlled intracellular replication of Mtb in HIV MDSC. These results demonstrate that MDSC in fully suppressed HIV-infected individuals are permissive to Mtb and exhibit downregulated anti-mycobacterial innate immune activity through mechanisms involving IL-27 and TLR signaling. Our findings suggest MDSC as novel mediators of tuberculosis in HIV-Mtb co-infected individuals with virologic suppression.